Rhinoscleroma Causing Upper Airway Obstruction - Geetika Verma; D Kanawaty; R Hyland (Canadian Respiratory Journal)
Rhinoscleroma is a chronic granulomatous condition of the respiratory tract, and is not uncommon in tropical regions; particularly, Mexico, Central America and the Middle East. A few cases have been reported in North America, primarily involving immigrants from endemic countries. The causative organism is Klebsiella rhinoscleromatis, a Gram-negative coccobacillus. Diagnosis is made on the basis of culture of the organism and the characteristic pathology of Mikulicz cells on light microscopy. The condition primarily affects the upper airway, and frequently presents with nasal discharge, nasal obstruction or frontal facial pain. Despite the term 'rhinoscleroma', there may be involvement of the entire respiratory tract. Although the condition is slowly progressive, its natural course portends extensive destruction. Laryngotracheal involvement occurs in approximately 15% to 80% of cases, but patients rarely present with isolated laryngotracheal disease. In the present paper, a case of rhinoscleroma presenting with symptoms of upper airway obstruction is described.